1994
DOI: 10.1084/jem.179.2.757
|View full text |Cite
|
Sign up to set email alerts
|

Human interleukin 10 induces naive surface immunoglobulin D+ (sIgD+) B cells to secrete IgG1 and IgG3.

Abstract: SummaryDuring antigen-induced immune responses, human B cells switch isotype from immunoglobulin M (IgM)-IgD to IgG1-4, IgA1-2, or IgE. In the human, no cytokines have yet been demonstrated to act as switch factors for IgG1, IgG2, and IgG3. In this paper, we report that in response to interleukin 10 (IL-10), anti-CD40 activated tonsillar surface IgD + (slgD +) B cells are induced to secrete large amounts of IgM, IgG1, and IgG3 but neither IgG2 nor IgG4. Cord blood purified B cells and lymphocytes from Hyper-Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
163
1
8

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(183 citation statements)
references
References 23 publications
11
163
1
8
Order By: Relevance
“…This is consistent with the fact that IL-10 acts mainly as a switching factor from IgM to IgG (37). Thus, IL-10 might play a crucial role in the antigen-driven production of autoreactive IgG by B cells after interaction with T helper cells in RA patients.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the fact that IL-10 acts mainly as a switching factor from IgM to IgG (37). Thus, IL-10 might play a crucial role in the antigen-driven production of autoreactive IgG by B cells after interaction with T helper cells in RA patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, in contrast to IL-4, IL-10 also promotes the Ig switch to IgG3 [68]. The effect of CD4 + KJ1-26 + cells from tolerant mice on promoting IgG1 but not IgG3 suggests a Th2-type cell rather than a Tr1-type regulatory cell.…”
Section: Discussionmentioning
confidence: 94%
“…The cytokine IL-10 also induces the switch to IgG1 [68]. However, in contrast to IL-4, IL-10 also promotes the Ig switch to IgG3 [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic chagasic patients, IgG1 and IgG2 form about 90% of the IgG produced (Watthanakulpanich et al 2008). It has been demonstrated that Th1 cytokines (IL-12, IFN-γ, TNF-α) are responsible for the production of IgG1 and IgG3 isotypes, while Th2 cytokines (IL-4 and IL-10) stimulate IgG2 production (Briere et al 1994, Kawano et al 1994). IgG1 mediates lysis binding to complement C1q protein and macrophage phagocytosis, while IgG2 mediates immunity by non-phagocytic effectors cells (Fanger et al 1991).…”
mentioning
confidence: 99%